MANAJEMEN MUTU PENDIDIKAN TINGGI (MMPT): KONSEP DASAR DAN STRATEGI DALAM PENINGKATAN MUTU BERKELANJUTAN - Andi Arif Rifa'i (Sustainable, 2018)
Higher education quality management is a strategic concept that is able to bring a university to the world level. In the basic concepts of quality management, quality is always planned, controlled, guaranteed and continuously improved. Practical and strategic models such as TQM, EFQM, SQM and others, provide philosophical offers to managers who wish to improve the quality of their institutions. Providers of quality management models in higher education services must consider customer satisfaction as one of the main quality measures. The implementation of higher education will ultimately have an impact on the competitiveness of the nation's human resources.